Transcription dynamics of heat-shock proteins (Hsps) and endosymbiont titres in response to thermal stress in whitefly, Bemisia tabaci (Asia-I) - Barman, Mritunjoy; Samanta, Snigdha; Ahmed, Bulbul; Dey, Soumik; Chakraborty, Swati; Deeksha, M.G.; Dutta, Subham; Samanta, Arunava; Tarafdar, Jayanta; Roy, Deepayan (Frontiers in Physiology, 2023)
The sweet potato whitefly, Bemisia tabaci (Gennadius) is one of several species complex of whitefly that are currently important agricultural pests. B. tabaci infests more than 600 plant species and thrives in a wide range of temperature conditions. Besides the direct damage caused by sucking plant sap, it vectors several plant viruses. Heat shock proteins play a pivotal role in enabling the insect to extend its geographical location, survival and reproduction in different stress condition. B. tabaci harbours several endosymbionts under the genera Portiera, Rickettsia, Hamiltonella, Wolbachia, Arsenophonus, Cardinium and Fritschea that directly or indirectly affect its fitness. By accelerating cuticle biosynthesis and sclerotization, symbiotic microbes can reduce or enhance tolerance to temperature extremes, and detoxify heavy metals. Thus, symbionts or microbial communities can expand or constrain the abiotic niche space of their host and affect its ability to adapt to changing conditions. The present study delineates the effect of thermal stress on expression of heat shock genes and endosymbionts in B. tabaci. Study of the expression level of heat shock proteins with the help of quantitative real-time PCR (qRT-PCR) showed that heat and cold shock treatment fuels higher to increased expression of Hsps (Hsp40 and Hsp70). However, Hsp90 was not induced by heat and cold- shock treatment. A significant decrease in the relative titre of secondary endosymbionts, Rickettsia, Arsenophonus and Wolbachia were recorded in B. tabaci upon heat treatment. However, the titre of primary symbiont C.portiera were relatively unaffected by both cold and heat treatments. These results are indicative of the fact that Hsp genes and endosymbionts in B. tabaci are modulated in response to thermal stress, this might be responsible for adaptation of whitefly under changing climatic scenario.